2018
DOI: 10.1080/1360080x.2018.1478613
|View full text |Cite
|
Sign up to set email alerts
|

Doctoral students’ access to non-academic support for mental health

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 48 publications
6
84
0
4
Order By: Relevance
“…Improvements could be achieved in several ways. Waight and Giordano (2018) recommend clear signposting in buildings as well as online promoting mental health services, online self-help resources, proactive workshops designed to build resilience and sustain mental health (e.g., mindfulness training), institutional support groups for those at a higher risk of low support such as international students, and training supervisors about the role of nonacademic support for doctoral students.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements could be achieved in several ways. Waight and Giordano (2018) recommend clear signposting in buildings as well as online promoting mental health services, online self-help resources, proactive workshops designed to build resilience and sustain mental health (e.g., mindfulness training), institutional support groups for those at a higher risk of low support such as international students, and training supervisors about the role of nonacademic support for doctoral students.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of Evans, Bira, Gastelum, Weiss and Vanderford (2018) shows that this trend is found in the 26 countries of the study. It should be added that different comparisons reveal that PhD students are more depressed than other students or quali ed workers 2,3 .…”
Section: Theoretical Approachmentioning
confidence: 99%
“…To answer this issue, recent research suggests that their high levels of stress could be caused in part or exacerbated by aspects of the doctoral education environment ( eld of research, type of supervision, grant… for a complete review of these aspects, see Waight & Giordano, 2018). However, the particularity of this environment has not been explored in consistent enough ways to provide a clear way forward for universities and health services to respond to this issue.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Current understanding of the discrepancy between the increase in enrolments and completions within Australia is poor, as most research on student success in higher education has focused on domestic students at the undergraduate level [2]. However, research from North America, Canada and the UK identify several factors that may lead to study drop-out, such as high workload, funding pressures and supervisory relationships [3][4][5][6]. Such research has also highlighted that two critical factors are isolation and poor social support, which might have particularly strong effects for students who are relocating either internationally or across state lines and have added pressures of having to cope with new physical and cultural environments [7].…”
mentioning
confidence: 99%